Three reasons protein disorder analysis makes more sense in the light of collagen. (19th April 2016) - Smithers, Ben; Oates, Matt E.; Tompa, Peter; Gough, Julian
Abstract: We have identified that the collagen helix has the potential to be disruptive to analyses of intrinsically disordered proteins. The collagen helix is an extended fibrous structure that is both promiscuous and repetitive. Whilst its sequence is predicted to be disordered, this type of protein structure is not typically considered as intrinsic disorder. Here, we show that collagen‐encoding proteins skew the distribution of exon lengths in genes. We find that previous results, demonstrating that exons encoding disordered regions are more likely to be symmetric, are due to the abundance of the collagen helix. Other related results, showing increased levels of alternative splicing in disorder‐encoding exons, still hold after considering collagen‐containing proteins. Aside from analyses of exons, we find that the set of proteins that contain collagen significantly alters the amino acid composition of regions predicted as disordered. We conclude that research in this area should be conducted in the light of the collagen helix.